2008
DOI: 10.1158/0008-5472.can-08-0449
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Interleukin-4 Promotes Tumor Development by Increasing Tumor Cell Resistance to Apoptosis

Abstract: The increase of interleukin-4 (IL-4) level in tumor environment and the up-regulation of IL-4 receptor (IL-4R) on tumor cells have been long observed. However, their significance for tumor development has not been investigated. Here, we found that endogenous IL-4 promotes tumor growth because neutralizing IL-4 by 11B11 monoclonal antibody (mAb) significantly delayed the growth of MCA205 fibrosarcoma.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 36 publications
5
71
1
Order By: Relevance
“…In the presence of IL-4, these cells expressed high levels of cellular Bcl-x L , cFLIP or both of them. The investigators in our group observed the similar effects of IL-4 on murine fibrosarcoma (56), and using IL-4R competent or deficient tumor cells of the same origin demonstrated that IL-4 promotes tumor growth in vivo (Figure 2). …”
Section: Tumor Cells Express Elevated Amount Of Il-4rmentioning
confidence: 58%
“…In the presence of IL-4, these cells expressed high levels of cellular Bcl-x L , cFLIP or both of them. The investigators in our group observed the similar effects of IL-4 on murine fibrosarcoma (56), and using IL-4R competent or deficient tumor cells of the same origin demonstrated that IL-4 promotes tumor growth in vivo (Figure 2). …”
Section: Tumor Cells Express Elevated Amount Of Il-4rmentioning
confidence: 58%
“…A series of studies, including ours, demonstrate a critical requirement for IFN-␥ in tumor growth inhibition (10 -13). In addition, high levels of exogenous TNF-␣ or IL-4 also mediate the suppression of tumor growth through the IFN-␥ pathway (14,15), highlighting the key role of IFN-␥ in tumor immunity (10 -16). Consistent with the pleiotropic activities of this cytokine, the IFN-␥ receptor (IFN-␥R) is expressed on almost all cell types (17)(18)(19).…”
mentioning
confidence: 99%
“…IL-4 itself may affect tumor growth, especially on those that have abundant IL-4 receptors. The levels of expression of the IL-4 receptor correlated with the tumorigenic potential in a murine model (27). Several tumors appeared to be resistant to apoptosis, which is induced by chemotherapeutic agents or CD95 ligation, in an IL-4-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…IL-4 seemed to modify the immunological functions of effector cells. The cultivation of naïve CD8 + T cells in the presence of IL-4 resulted in poor cytolytic function in the cells by reducing the levels of perforin and granzymes (27,28). Whether an immune response is predominantly Th1 or Th2 may depend on a number of other factors, such as mouse strain, kind of tumor, amount of tumor antigen, and the amount of cytokine (29,30).…”
Section: Discussionmentioning
confidence: 99%